Mobile Devices and Research Work in Social Science - Said, MF; Adham, KA (Univ Putra Malaysia Press, 2024)
Mobile technologies have long been adopted in pure science research. However, their use in social science research has been largely ignored. The objective of this study is to understand how mobile devices support social science research. To achieve this purpose, we adopted observation as a methodology to determine actual usage of mobile devices by ten individuals involved in research works, including research administrators, researchers, and research assistants. Our findings indicate that social science researchers use mobile devices to support the task of reviewing literature and gathering data. The use of mobile devices also broadens the researchers' abilities to capture and store multimedia research data and facilitates data access and analysis. Researchers also utilise mobile devices to support the management of their research projects, including communicating with other researchers and coordinating activities amongst them. They also optimize mobile devices in planning, organizing, leading and controlling their research process. In conclusion, mobile devices have become increasingly useful as multitask tools for researchers, and h